Floods and firms: Vulnerabilities and resilience to natural disasters in Europe - Serena Fatica; Gábor Kátay; Michela Rancan (European Commission, 2022)
Combining a rich database on natural hazards, granular flood risk maps and detailed information on firm geolocalisation, we study the dynamic impacts of floods on European manufacturing firms during the period 2007-2018. We find that water damages significantly and persistently worsen firm performance, and may endanger their survival. An average flood deteriorates total assets by about 2% in the year after the event, and up to 5% seven years out. The drop in sales and employment is comparable. We show how reallocation of economic activity within flooded regions can reconcile our results with the 'creative destruction' hypothesis proposed by the natural disaster literature.
Keywords: D22; Q54; R11; 330; natural disasters; floods; climate risk; firm performance; panel local projections